Selecting Graduate Supervisors in Islamic Higher Education: Bridging Educational Theory, Ethics, and Multicultural Practice - Awad Mabrouk (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to investigate the process of selecting supervisors for master's and doctoral theses as a cornerstone of graduate program success. It specifically seeks to identify the gap between theoretical academic regulations and actual field practices in Arab universities compared to international standards. Theoretical framework: The research is grounded in the